PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN APLIKASI GOJEK ONLINE DI KOTA MAKASSAR - Saputra, Adam Wahyu; Ilham, Ilham; Murbayani, Murbayani (Patria Artha University, 2022)
This study aims to determine the effect of Service Quality and Price on Customer Satisfaction. This research was conducted with an explanatory approach (explanatory research) which seeks to explain the effect of causality (causality relationship) and explain the effect of causality between the independent variables (service quality and price), and the dependent variable (customer satisfaction), the online Gojek application in Makassar and data. These were analyzed by means of multiple linear regression analysis. This type of research is based on the method using descriptive research through a quantitative approach. The population in the study were 100 online Gojek application customers in Makassar. The sampling technique in this study was accidental sampling, where the researcher took the sample encountered at the time of the study. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis using multiple linear regression analysis methods. The results of the research indicate that Service quality has a significant effect on customer satisfaction, Price has a significant effect on customer satisfaction and Service Quality and Price simultaneously has a significant effect on customer satisfaction.